Agglomeration of Natural Fibrous Materials in Perpetual Screw Technique – A Challenge for Designer - Talaśka, Krzysztof; Malujda, Ireneusz; Wilczyński, Dominik (Procedia engineering, 2016)
The paper presents the characteristics of consolidation of natural fibrous materials for getting the renewable solid fuel. A special attention was focused on the perpetual screw technique. A detailed analysis of the consolidation process for this technique allowed to find its advantages and drawbacks. Economic reasons for this technique are also presented. Detailed characteristics of the process allowed to separate the stages when the designer can improve the construction and get the higher efficiency of the consolidation process of the material. Design algorithm for designers of such type of machines is presented.